2016
DOI: 10.1080/19440049.2016.1217065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary acids on the formation of aflatoxin B2a as a means to detoxify aflatoxin B1

Abstract: Aflatoxin B1 (AFB1) is a class 1 carcinogen and a common food contaminant worldwide with widely uncontrolled human exposure. The ability of organic acids to transform AFB1 into a known detoxified form, aflatoxin B2a (AFB2a), was investigated using high performance liquid chromatography-electrospray ionisation-time of flight mass spectrometry (HPLC/ESI/TOF/MS). The identity of the transformation product was confirmed by accurate mass measurement, chromatographic separation from other aflatoxins, H(1)-nuclear ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Because AFB1 can be transformed into AFB2a which can then adduct to amines under acidic conditions, we investigated the transformation of AFB1 into AFB2a-Arg in a single treatment step across multiple acidic pH values. In previous work, we found that by adding various concentrations of citric acid into simulated gastric fluid, the transformation of AFB1 into AFB2a was greatly enhanced even though the pH remained unchanged [ 25 ]. Therefore, we also tested the effect of having either citric acid, phosphoric acid, or both present in the solution at each pH level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because AFB1 can be transformed into AFB2a which can then adduct to amines under acidic conditions, we investigated the transformation of AFB1 into AFB2a-Arg in a single treatment step across multiple acidic pH values. In previous work, we found that by adding various concentrations of citric acid into simulated gastric fluid, the transformation of AFB1 into AFB2a was greatly enhanced even though the pH remained unchanged [ 25 ]. Therefore, we also tested the effect of having either citric acid, phosphoric acid, or both present in the solution at each pH level.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our lab has investigated the efficacy of common organic acids or acidic environmental conditions to transform AFB1 into aflatoxin B2a (AFB2a) - an AFB1 metabolite which has shown to have reduced mutagenicity due to hydration of the 8,9-double bond [ 25 27 ]. Although in vivo data is limited, AFB2a has still been shown to have some hepatotoxic effects at high doses and there is a concern for its ability to spontaneously dehydrate back to AFB1, so its role as a detoxification end-product is unclear [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this binding only occurs on primary amines that is favored in alkaline pHs. This adduction can also occur on phosphoethanolamine head groups on phospholipids, forming a unique structurally characterized aflatoxin-lipid adduct [61]. The protein-binding capability of AFB2a is thought to contribute to other potential cellular toxicities.…”
Section: The Metabolism and Toxic Mechanism Of Afb1mentioning
confidence: 99%
“…These methods have been observed to have high reduction rate in less than 24 h even at room temperature. The conducting process is also simple, just requiring to soak contaminated foods in acidic solutions for a given amount of time [61,122,123]. Unlike biological degradation, the detoxification product of AFB1 in acid is AFB2a as mentioned above, which is widely recognized as a far less toxic metabolite of AFB1.…”
Section: Detoxification Strategiesmentioning
confidence: 99%
“…Therefore, lactic acid can be recommended for food processing and as a preservative in fermented foods [49]. Rushing and other studies have shown that under acidic conditions, organic acids and arginine can be mixed to treat contaminated foods, and AFB1 can be rapidly converted to AFB2a-Arg within 20 minutes, reducing toxicity [50][51][52][53]. Aly et al showed that HCL can effectively degrade AFB1 during acid hydrolysis [54].…”
Section: Chemical Treatmentmentioning
confidence: 99%